Layering‐Triggered Delayering with Exfoliated High‐Aspect Ratio Layered Silicate for Enhanced Gas Barrier, Mechanical Properties, and Degradability of Biodegradable Polymers (Global Challenges 9/2020). Issue 9 (3rd September 2020) - Zhu, Jian; Kumar, Anil; Hu, Pin; Habel, Christoph; Breu, Josef; Agarwal, Seema
Abstract : In article number 2000030, Seema Agarwal and co‐workers achieve the enhanced degradability, modulus, and decreased oxygen permeability required for packaging in polylactide (PLA) by making its composites with exfoliated sodium hectorite (Hec) in a layer‐by‐layer structure. The layered structure enables improved mechanical and gas permeation properties, while the delayering of composite films due to the swelling of Hec provide accelerates degradation.